(untitled) (Bulletin of the International Association for Paleodontology, 2022)
Introduction: The variation observed when studying odontometrics has immensely contributed over time to the investigation of hominid evolution and the population groups’ diversity, according to their geographic distribution. The present study consists in the evaluation of odontometrics belonging to commingled human remains found in Academia das Ciências de Lisboa from the 1755 Lisbon’s Earthquake. Aims: The first purpose is to comprehend if the odontometrics obtained in this study’s sample fit its time and region, through the comparison of other populations in different locations. The second one is focused on the analysis of odontometrics’ evolution through time, in the same region. Materials and methods: The whole sample of 1479 teeth was weighed and measured through three diameters: mesiodistal (MD), buccolingual/buccopalatine (BP/BL) and crown height (CH). Results: The average values of mesiodistal and buccolingual diameter of upper incisors are respectively, 8.200 mm and 7.021 mm for the central incisor, and 6.296 mm and 6.209 mm for the lateral. The upper canine has an average value of mesiodistal diameter of 7.435 mm and an average value of buccolingual diameter of 8.016 mm. The measurements revealed a high concentration of observations with values close to the median and few observations with distant values (very few outliers). Conclusion: Odontometrics obtained in Lisboa’s sample are within the expected standards for that epoch. Plus, the results captured in recent studies reveal MD and BP/BL diameters values slightly high.